2019
DOI: 10.1016/j.jtho.2018.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Lung Adenocarcinomas Manifesting as Radiological Part-Solid Nodules Define a Special Clinical Subtype

Abstract: Introduction:The clinicopathologic features and prognostic predictors of radiological part-solid lung adenocarcinomas were unclear. Methods:We retrospectively compared the clinicopathologic features and survival times of part-solid tumors with those of pure ground glass nodules (pGGNs) and pure solid tumors treated with surgery at Fudan University Shanghai Cancer Center and evaluated the prognostic implications of consolidation-to-tumor ratio (CTR), solid component size, and tumor size for part-solid lung aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
156
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(168 citation statements)
references
References 24 publications
9
156
3
Order By: Relevance
“…19 A different approach, the mixture cure model, was thus employed in this study to investigate the long-term prognostic potential of nodule type. Our study results, which partly coincide with those of past studies, 6,7 reported that the nodule type (i.e., PSN) could be used as a long-term prognostic indicator for surgical candidates with clinical stage IA adenocarcinomas. One may argue that the solid portion size would be different between PSNs and solid nodules even in the same cT category and that such discrepancy would be the potential confounder.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…19 A different approach, the mixture cure model, was thus employed in this study to investigate the long-term prognostic potential of nodule type. Our study results, which partly coincide with those of past studies, 6,7 reported that the nodule type (i.e., PSN) could be used as a long-term prognostic indicator for surgical candidates with clinical stage IA adenocarcinomas. One may argue that the solid portion size would be different between PSNs and solid nodules even in the same cT category and that such discrepancy would be the potential confounder.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a few studies reported the distinct prognosis of PSNs compared with that of solid nodules. [5][6][7] Aokage et al 5 compared the overall survival (OS) of patients with clinical stage I, resected adenocarcinomas characterized by PSNs and solid nodules and revealed that those with PSNs had a more favorable prognosis in clinical stages IA2 and IA3. In addition, Ye et al 6 reported the excellent prognosis of patients with resected adenocarcinomas that appeared as PSNs in clinical stage IA and reported that neither the solid portion size nor the total tumor size could predict the prognosis of PSNs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, according to Hattori et al, 34 the presence of a GGO component had a strong influence on the prognosis, more than the size of the solid component. Ye et al 15 also found a better survival in patients with subsolid appearance compared with those with solid tumors on HR-CT imaging but had no prognostic features in the subsolid nodules. Possibly, tumor atelectasis may provide an explanation for this finding.…”
Section: Discussionmentioning
confidence: 97%